Electronic Word-of-Mouth and Social Media Marketing on Brand Image and Purchase Intention - Kartika, Tasia; Pandjaitan, Dorothy (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Electronic Word-of-Mouth (eWOM) and Social Media Marketing are widely used by consumers to gather information about a product. Information obtained from various sources on the internet will affect consumer perceptions of brand image, risk and encourage consumer buying interest. This study aims to examine the effect of electronic word-of-mouth variables, and social media marketing on purchase intention with brand image as an intervening variable. This research was conducted quantitatively on 150 respondents. The research was conducted on all Lampung people who know about Bittersweet by Najla Lampung on Instagram and have made purchases through e-commerce. The method used is Structural Equation Model with SmartPLS 3.3.3 software in 2023. Statistical results after hypothesis testing show that each variable, namely: These results indicate that hypotheses one, two, three, four and five are proven, and it can be concluded that electronic word-of-mouth has a positive and significant effect on brand image and purchase intention, and social media marketing has a positive effect on brand image and purchase intention and is significant to brand image and significant to purchase intention. Meanwhile, brand image has a positive and significant effect on purchase intention.